The Disunity of Disease - Hane Htut Maung (Philosophy of Medicine, 2025)
In a recent paper, Harriet Fagerberg argues that the disease debate in the philosophy of medicine makes little sense as conceptual analysis but instead should proceed on the assumption that disease is a real kind. I propose an alternative view. The history and practice of medicine give us reasons to doubt that the category of disease forms a real kind. Instead, drawing on work by Quill R. Kukla, I argue that the disease debate makes good sense on an understanding of disease as an institutional kind. As well as explaining key features of the disease debate, this can facilitate a philosophical understanding of disease that captures the eclectic scope of medicine and the complex reasons why conditions get classified as diseases.